HUBUNGAN KOUNIKASI SBAR DENGAN PELAKSANAAN TIMBANG TERIMA PERAWATDI RUANG RAWAT INAP RSUD Dr. A. DADI TJOKRODIPO BANDAR LAMPUNG TAHUN 2019 - Reva Monica (Fakultas Ilmu kesehatan UPN Veteran Jakarta, 2019)
THE CORRELATION OF THE SBAR COMMUNICATION WITH THE IMPLEMENTATION OF HANDOVER NURSES AT CARE WARDS OF A DADI TJOKRODIPO HOSPITAL OF BANDAR LAMPUNG IN 2019 Background: The implementation of handover is often a problem in several hospitals, the results of interviews conducted in the inpatient room, of 3 head of the room and 3 team leaders, and 2 people in charge of the operand shift. Said that the handover using SBAR communication has been established since 2017. However, the handover is not yet running optimally. The results of the assessment of the implementation of handover nursesusing SBAR communication, from 8 nurses, 5 nurses (62.5%) with the implementation of the handover was not good, and 3 nurses (37.5%) with a well-received balance. Objective: Known the correlation of SBAR communication with the implementation of handover nurses in the inpatient room of RSUD Dr. A. Dadi Tjokrodipo Bandar Lampung in 2019. Methods: This type of research is quantitative. The design of this research was the analytic survey with a cross-sectional approach. The population and sample used are all nurses in the inpatient room as many as 50 people. Sampling in the study is total sampling Statistical tests using the chi-square test Results: The results of data analysis using the chi-square test obtained p-value = 0.008 (<0.05) which means that there is a relationship between communication SBAR with the implementation of handover nurses in the Inpatient Room Dr. A. Dadi Tjokrodipo Bandar Lampung in 2019 with an OR value = 6.120. Conclusion: There is a correlation between SBAR communication and the acceptance and evaluation process at RSUD Dr. A TjokrodipoBandarLampung. Suggestions for health institution services to make the shift every shift/operand, prepare nursing problems that still arise and interventions that have not been done and prepare general plans and preparations that need to be done. For nurses do not explain right beside the patient in a loud voice, do not use standard language so that it is easily understood by patients, and introduce themselves to patients when doing SBAR. Keywords : SBAR Communication, Implementation of Handover Nurses Pendahuluan: Pelaksanaan timbang terima seringkali menjadi permasalahan di beberapa Rumah Sakit, hasil wawancara yang dilakukan di ruang rawat inap, terhadap 3 orang kepala ruangan dan 3 orang ketua tim, serta 2 orang penanggung jawab operan shift. Mengatakan bahwa timbang terima menggunakan komunikasi SBAR sudah ditetapkan sejak tahun 2017.Namun pelaksanaan timbang terima belum berjalan dengan optimal. Hasil penilaian tentang pelaksanaan timbang terima menggunakan komunikasi SBAR, dari 8 perawat, 5 perawat (62.5%) dengan pelaksanaan timbang terima kurang baik, dan 3 orang perawat (37.5%) dengan timbang terima baik. Tujuan: Diketahui hubungan komunikasi SBAR dengan pelaksanaan timbang terima perawat di ruang rawat inap RSUD Dr. A. Dadi Tjokrodipo Bandar Lampung Tahun 2019. Metode: Jenis penelitian ini adalah Kuantitatif. Desain penelitian ini survey analitik dengan pendekatan cross sectional. Populasi dan sampel yang digunakan adalah seluruh perawat di ruang rawat inap yaitu sebanyak 50 orang. Pengambilan sampel pada penelitian adalah total sampling Uji statistik menggunakan uji chi square Hasil :Hasil analisa data menggunakan uji chi square didapat nilai p-value = 0.008 (<0,05) Yang artinya adahubungan komunikasi SBAR dengan pelaksanaan timbang terimaperawat di Ruang Rawat Inap RSUD Dr. A. Dadi Tjokrodipo Bandar Lampung Tahun 2019. dengan nilai OR = 6,120. Kesimpulan : Ada hubungan antara komunikasi SBAR dengan pelaksanaan timbang terima di RSUD Dr. A Tjokrodipo Bandar Lampung. Saran kepada pelayanan institusi kesehatan untuk melakukan operan setiap pergantian shift/ operan, mempersiapkan masalah keperawatan yang masih muncul dan intervensi yang belum dilakukan, serta menyiapkan rencana umum dan persiapan yang perlu dilakukan. Bagi perawat tidak menjelaskan tepat disamping pasien dengan suara lantang, tidak menggunakan bahasa yang baku sehingga mudah dipahami oleh pasien, dan memperkenalkan diri kepada pasien saat melakukan SBAR.